2020
DOI: 10.1371/journal.pone.0234422
|View full text |Cite
|
Sign up to set email alerts
|

Potentials and pitfalls of increasing prosocial behavior and self-efficacy over time using an online personalized platform

Abstract: Background This longitudinal mixed methods experimental study aimed to better understand the interplay between digital technology exposure over time, self-efficacy, and prosocial behavior in everyday contexts. Methods 66 psychology students tracked their daily prosocial behavior over three weeks. Additionally, half of the participants were randomly assigned to receive access to an online platform, which made personalized suggestions for prosocial actions to complete. Qualitative poststudy interviews complement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 66 publications
0
3
0
1
Order By: Relevance
“…This situation can generally be linked to any arena of social behavior, but it seems more vividly to the environmental aspect, where global warming is linked to individual actions by reducing the use of cars, conserving energy and reducing waste. Steinemann, Geelan, Zaehringer, Mutuura, Wolkow, Frasseck, and Opwis (2020) reported that the degree to which a given behavior would be undertaken to have a tangible effect. Citizens who believed that their actions could make any significant difference to waste issues were those who were more likely to act.…”
Section: Perceived Behavioral Control and Waste Segregation-at-sourcementioning
confidence: 99%
“…This situation can generally be linked to any arena of social behavior, but it seems more vividly to the environmental aspect, where global warming is linked to individual actions by reducing the use of cars, conserving energy and reducing waste. Steinemann, Geelan, Zaehringer, Mutuura, Wolkow, Frasseck, and Opwis (2020) reported that the degree to which a given behavior would be undertaken to have a tangible effect. Citizens who believed that their actions could make any significant difference to waste issues were those who were more likely to act.…”
Section: Perceived Behavioral Control and Waste Segregation-at-sourcementioning
confidence: 99%
“…Hasil studi tersebut sejalan dengan hasil studi yang dilakukan pada relawan sosial di empat kota Asia (Pandya, 2020), and those of a study performed in Indonesia with teachers, by Hanisah et al (2019). Although this is the case, there are contradictory study results related to connections between these two variables, such as the results in a study by Steinemann et al (2020), which stated that prosocial behavior, in any form at all, cannot be predicted from selfefficacy. This number of mutually contradictory and inconsistent study results became a powerful rationale for the authors to re-test relationships between the two variables, in this study.…”
Section: Efikasi Diri Dan Perilaku Prososialmentioning
confidence: 95%
“…Hypothesis 4: There is a role between the egoistic motives and prosocial behavior of flood Tengah (Pandya, 2020) dan hasil studi di Indonesia pada guru oleh Hanisah et al (2019). Walaupun demikian, ada hasil studi yang bertentang sehubungan hubungan kedua variabel ini, seperti hasil studi Steinemann et al (2020) yang menyatakan bahwa perilaku prososial dalam bentuk apapun tidak dapat diprediksi oleh efikasi diri. Sejumlah hasil studi yang saling bertentangan dan inkonsisten ini memberikan alasan kuat bagi penulis untuk menguji kembali hubungan kedua variabel pada studi ini.…”
Section: Egoistic Motiveunclassified
“…The environmental aspect of this problem stems from the belief and perception that personal behaviour execution can reduce pollution. Furthermore, [49] determined the probability that a specific behaviour would be portrayed in order to have an influence that could be felt. Therefore, due to the existing research that provides numerous positive relationship results on perceived behavioural control and actual behaviour, the following theory is put forth.…”
Section: Perceived Behavioural Control and Sustainable Waste Manageme...mentioning
confidence: 99%